2022
DOI: 10.7759/cureus.28229
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein as a Predictor of Severity in Chronic Obstructive Pulmonary Disease: An Experience From a Tertiary Care Hospital

Abstract: Background In this study, we aimed to determine the frequency of raised C-reactive protein (CRP) levels and their association with the severity of the disease. Methodology This descriptive cross-sectional study was conducted at the Shifa International Hospital, Islamabad, from June 2018 to December 2018 in the Department of Medicine. Patients attending the respiratory outpatient clinic in the Department of Medicine, Shifa International Hospital, Islamabad, with chronic obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…This analysis of NHANES and NDI data suggests that while having COPD increases the risk of mortality, elevated CRP levels may further increase the risk of mortality among those with COPD. Previous studies have suggested the role of inflammation in the pathogenesis, progression, and exacerbation of COPD by assessing CRP [4][5][6]15]. Some studies have also found CRP to have a high predictive value in diagnosing exacerbations of COPD [1,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis of NHANES and NDI data suggests that while having COPD increases the risk of mortality, elevated CRP levels may further increase the risk of mortality among those with COPD. Previous studies have suggested the role of inflammation in the pathogenesis, progression, and exacerbation of COPD by assessing CRP [4][5][6]15]. Some studies have also found CRP to have a high predictive value in diagnosing exacerbations of COPD [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, chronic obstructive pulmonary diseases (COPD) are now among the top 3 leading causes of death with more than 3 million deaths per year and more than 50 million living with the disease [1-3]. While it is well established that COPD is a progressive disease resulting from persistent and abnormal inflammatory processes damaging the lung tissue, the search for definitive and distinct biomarkers for the disease continues [2][3][4][5]. A plethora of studies in recent times have shared genetic and biochemical data for individuals with COPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pCRP is mostly considered to be a marker of inflammation, bacterial infection or sepsis, it was established early on that pCRP levels increase during SARS-CoV-2 infection ( 17 , 18 , 20 , 23 ). Persistent elevated plasma levels of pCRP are found in chronic inflammatory diseases such as rheumatoid arthritis ( 3 ), type 2 diabetes mellitus, and Parkinson’s disease ( 29 ), and in chronic obstructive pulmonary disease ( 30 ). Whether mCRP levels are elevated in these diseases is not known, but mCRP has been implicated to play a pathogenic role in cardiovascular disease where it is detected in atherosclerotic plaques, and to cause neuroinflammation where it is found in the affected neuronal tissue ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…С-реактивний білок -це сполука, вміст якої збільшується в плазмі крові при різних запальних станах. Результати досліджень вказують на те, що навіть пацієнти зі стабільним перебігом ХОЗЛ мають підвищені рівні С-реактивного білка у сироватці крові, що корелює з тяжкістю хвороби, а також може корелювати з виникненням ускладнень [2]. Саме тому перспективним є аналіз кореляційних зв´язків рівня С-реактивного білка у крові із іншими клінічними, лабораторними, інструментальними показниками у пацієнтів з ХОЗЛ.…”
unclassified